2014
DOI: 10.5934/kjhe.2014.23.2.269
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Family Violence Exposure on School Violence among Adolescents: Mediating Effects of Life Satisfaction, School Life Satisfaction, & Internalizing

Abstract: The purpose of this study was to examine the relationship between family violence exposure and school violence, to explore the mediating effects of family life satisfaction, school life satisfaction, and internalizing on those relationship and to suggest practical implications for social work services for those adolescents. 4,773 adolescents were selected for the questionnaire study in Gjwangju. Collected data were analysed by Structural Equation Modeling in AMOS 20.0 and SPSS 20.0. The findings of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…In previous studies, IPV has also been reported to have a negative impact on children's health and developmental processes (Evans et al, 2008;Holmes et al, 2015 ). The problematic behavior of children exposed to IPV should be addressed because unresolved problems in childhood lead to greater social problems when they are adults (Kim, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous studies, IPV has also been reported to have a negative impact on children's health and developmental processes (Evans et al, 2008;Holmes et al, 2015 ). The problematic behavior of children exposed to IPV should be addressed because unresolved problems in childhood lead to greater social problems when they are adults (Kim, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Children's behavioral problems do not only occur at the time of exposure to domestic violence, but can also become social, behavioral, and mental problems (Holmes et al, 2015;Rosser-Limiñana et al, 2020;Sonego et al, 2018 ), causing psychological and social maladjustment in their social lives (Kim, 2014). These children display higher levels of internalized problems (e.g., depression and anxiety) and external-ized behaviors (e.g., increased violence and aggression) than children of the same sex and age ranges with mothers who have not experienced domestic violence (McFarlane et al, 2003;Renner & Boel-Studt, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents' social maladjustment, including social deviance, has mostly been caused by parents' wrong guidance or improper relationship with parents, such as child abuse, indifference, or verbal violence [5]. The negative attitude that parents show when they raise their children has a negative effect on adolescents' psychosocial adjustment, which is highly likely to lead to various juvenile problems: running away from home, dropping out of school, or school violence [5].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents' social maladjustment, including social deviance, has mostly been caused by parents' wrong guidance or improper relationship with parents, such as child abuse, indifference, or verbal violence [5]. The negative attitude that parents show when they raise their children has a negative effect on adolescents' psychosocial adjustment, which is highly likely to lead to various juvenile problems: running away from home, dropping out of school, or school violence [5]. When parents use corporal punishment, reject or show an indifferent attitude, are not satisfied with their children, or display authoritarian or an inconsistent attitude of parenting, children were found to show problematic attitudes such as expressions of anger, not being obedient, or having a low ability to control emotion [6].…”
Section: Introductionmentioning
confidence: 99%